10 minute guide to Lotus 1-2-3 release 2.3 - Murray, Katherine; Sabotin, Doug (Indiana : SAMS, 1991)
The 10 Minute Guide series is a new approach to learning computer programs. Instead of trying to teach your everything about a particular software product (and ending up with an 800-page book in the process), the 10 Minute Guide covers the most often-used features in 20 to 30 short lessons.
1. Starting Lotus 1-2-3 -- 2. Exploring the Lotus Screen -- 3. Using Menus and Dialog Boxes -- 4. Entering Data -- 5. Saving the Worksheet and Exiting 1-2-3.
Includes index.
Keywords: LOTUS 1-2-3 (COMPUTER FILE)